ASYMMETRIES OF PUBLIC FINANCES UNDER STATE INCOME FORMATION UNCERTAINTIES (World of finance, 2025)
Introduction. The spread of geopolitical conflicts and hybrid wars, the diversity and asymmetries of global trends, migration crises, digitalization, the expanding use of artificial intelligence, and changes in climatic conditions underscore the necessity for discussions among policymakers, scholars, and concerned citizens to understand the impact of these factors on the fiscal space of public finances. A comprehensive SWOT analysis of global uncertainties allows for an understanding of their threats and consequences, aiding in the formulation and implementation of effective fiscal policy institutions as preventive tools to mitigate negative outcomes for citizens.The purpose of the article is to explore the challenges of forming the revenue side of the state budget in the context of transformations in tax and non-tax revenues through the lens of global uncertainties and to outline modern trends in shaping the fiscal space of the state.Results. Innovative approaches to identifying modern trends in fiscal policy space have been substantiated. The possibilities of tax and non-tax revenue contributions to budgets under global uncertainties and wartime conditions have been analyzed. The study examines the potential for optimally combining state and domestic borrowings as an alternative to tax-based revenue sources. Mathematical modeling vectors are outlined to account for force majeure circumstances, such as military actions, changes in factor prices, inflation, and capital stock depletion, to balance the expenditure component of public finances. The necessity of shifting priorities from external borrowings to internal ones has been scientifically proven to stabilize monetary and fiscal policies.Conclusions. The study deals with the impact of global uncertainties on contemporary trends in the fiscal policy information space. It differentiates between the effects of external and internal state borrowings on the transfer of fiscal burdens to future generations. Through mathematical modeling of trends and risk assessments associated with global military threats and global economic instability, the research explores possible strategies for adapting and optimizing fiscal measures in the context of a balanced combination of taxes and state borrowings.